Cultural Diplomacy: The Role of Indonesian Artists and Musicians in Supporting Palestine (Palestine Issues on Indonesian Society, 2024)
This paper examines the role of Indonesian artists and musicians in advocating for Palestine through cultural diplomacy. From music concerts to art exhibitions, Indonesian cultural figures have long used their platforms to raise awareness of Palestinian issues, drawing connections between their own history of struggle and the Palestinian cause. The paper analyzes how artists and musicians in Indonesia have contributed to global cultural solidarity movements, using art, music, and public performances as a means of fostering dialogue and raising awareness about the Palestinian struggle. By focusing on key cultural initiatives, this study highlights the impact of creative expression in shaping public opinion and diplomatic discourse. Furthermore, the paper explores how cultural diplomacy has facilitated Indonesia’s position as a key advocate for Palestine on the international stage, reinforcing the country’s identity as a proponent of justice and human rights. The research also considers the role of Indonesian cultural institutions in promoting solidarity with Palestine, both domestically and internationally.